If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+2=4(x+5)
We move all terms to the left:
3x+2-(4(x+5))=0
We calculate terms in parentheses: -(4(x+5)), so:We get rid of parentheses
4(x+5)
We multiply parentheses
4x+20
Back to the equation:
-(4x+20)
3x-4x-20+2=0
We add all the numbers together, and all the variables
-1x-18=0
We move all terms containing x to the left, all other terms to the right
-x=18
x=18/-1
x=-18
| 8x+3x=6x-3 | | 1.5x÷2=9.5 | | 3x-6-2x3=-12 | | (0.50m+15)=(25+0.25m) | | 8y+2=2y-26 | | 2x/3-7=-x/2 | | −0.8x−8.3=12.7 | | 20,000=x+1.15x | | 2.5(2z+5)=5(z+ | | 12(2w-3)+4w+6=-58 | | 42x2x6=12 | | 5m-8-6m=-11 | | 4.5a=81 | | 6f+7=26 | | 58-8z=30z-75 | | {a}{2}+6=-8 | | 3(3x+1/3)=5x+19 | | 6x(x+15)=0 | | 15-y=1 | | -5(x+2)^2=-500 | | 6(6v+6)–5=1+6v | | 9x+3x+18=0 | | 27-3r=3r+27 | | F(5)=8x+2 | | 55=−6d+7 | | 3(4z-8=-21+12z | | -x/4–2=X+3 | | 12y-15=45 | | (3)/(2)(16n+3)=24n | | -x/4–2=+3 | | 48=5x-11 | | 3(-2)-5(x-1)=-7 |